2003
DOI: 10.1590/s0004-282x2003000500003
|View full text |Cite
|
Sign up to set email alerts
|

Panic disorder in a breath-holding challenge test: a simple tool for a better diagnosis

Abstract: -Objective: Our aim was to observe if anxiety disorder patients -DSM-IV -respond in a similar way to the induction of panic attacks by a breath-holding challenge test. Method: We randomly selected 29 panic disorder (PD) patients, 27 social anxiety disorder (SAD) patients, 21 generalized anxiety disorder (GAD) patients. They were induced to breath-hold for as long as possible four times with two-minute interval between them. Anxiety scales were applied before and after the test. Results: A total of 44.8% (n=13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Several studies have investigated respiratory symptoms in PD patients [2], [31], [32], [33] and found that, during PA, respiratory complaints are common, such as dyspnea and tachypnea. Some specific respiratory tests aimed at inducing PA have been used, demonstrating that respiratory maneuvers, such as hyperventilation [34], carbon dioxide inhalation [35] and voluntary apnea [36], may increase anxiety in PD patients and thereby trigger a PA. In this regard, several studies have contributed to better understand the relationship between respiration and PA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated respiratory symptoms in PD patients [2], [31], [32], [33] and found that, during PA, respiratory complaints are common, such as dyspnea and tachypnea. Some specific respiratory tests aimed at inducing PA have been used, demonstrating that respiratory maneuvers, such as hyperventilation [34], carbon dioxide inhalation [35] and voluntary apnea [36], may increase anxiety in PD patients and thereby trigger a PA. In this regard, several studies have contributed to better understand the relationship between respiration and PA.…”
Section: Discussionmentioning
confidence: 99%
“…The BH test is a standardized procedure used to induce panic‐like symptoms under controlled laboratory conditions via an endogenous CO 2 increase . The duration of maximal BH is thought to reflect tolerance to CO 2 or physical sensations, with shorter times reflecting lower tolerance .…”
Section: Methodsmentioning
confidence: 99%
“…Klein (5) proposed the existence of an evolved "false suffocation alarm" system that triggers spontaneous panic attacks when the brain erroneously signals a lack of useful air and activates maladaptive autonomic responses to suffocation. Sensitivity to CO 2 might play a role in this hypersensitive suffocation detector, (5) and various respiratory tests, such as carbon dioxide inhalation, (6) hyperventilation (7) and breathholding, (8) have been fruitful in generating hypotheses about panic disorder. (3,5) Panic disorder patients exhibit behavioral and physiological abnormal responses to respiratory challenge tests that are very similar to those experienced during spontaneous panic attacks.…”
Section: Introductionmentioning
confidence: 99%